ANALISIS PERILAKU AKSES PENUMPANG PESAWAT DAN MODELPEMILIHAN WAKTU KEBERANGKATAN DENGAN MODA KERETA DI BANDARA: Studi Kasus: Bandara Adisutjipto, Yogyakarta - , Yogi Prasetya ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Air passenger background differences and airport check in rules bring contribution to the differences of air passenger access behaviour. In general, people plan their departure so they do not arrive late and also do not spend too much time for waiting. It brings impact to transport mode choices, which passengers will choose a transport mode which has maximum utility, so they get maximum advantages from it. Rail transport is one of the sustainable transport modes which is very interesting to be investigated in case of departure time decision and about how passengers minimize their disutility when depart from home to airport. This research identifies air passenger arrival time and classifies it according to the mode types. In order to understand the relationship between arrival-travel timedistance, Spearman correlation analysis has been conducted. Access mode choice was modelled by Multinomial Logistic method according to each modeâs utilities. The model result will be compared with the observation data. The rail passenger departure time model was conducted using Random Disutility Minimizing Method, including late departure disutility and rail disutility. The result shows that most of passengers arrive at airport in 120-60 minutes before air departure time. There is a difference between private and transit arrival curve. Transit passengers decide their departure time more carefully, so they arrive at airport early. There are insignificant correlations between arrival-distance and arrival-travel time, which are 0.182 and 0.238. The public choice model is more difficult to be done because there are some external factors which are not included in the model. The departure time decision model shows that rail users arrive at airport in interval 120-80 minutes. This high number of waiting time may caused by low level of rail reliability and because there are just a few departure schedule time in station. Keywords: behaviour, arrival time, access mode, utility, rail, disutility